An investigation of coupled natural human systems using a two-way coupled agent-based modeling framework. (September 2022) - Lin, Chung-Yi; Yang, Y.C. Ethan; Malek, Keyvan; Adam, Jennifer C.
Abstract: Improving the understanding of coupled natural human systems (CNHS) can better inform environmental policymaking. We investigated the co-evolution ( i.e., bidirectional interactions) issues in CNHS via two-way coupling RiverWare (RW; a river-reservoir routing model) with agent-based models (ABMs, human decision models) in the Yakima River Basin in Washington, US. Results show that coupled models can better capture the historical irrigation diversion (human) and streamflow (nature) dynamics. We further demonstrated the effect of social norms ( i.e., the influence of neighbors) among farmers and tested a "water reallocation" scenario to evaluate the influence of water policies on irrigation diversion behaviors. Detailed model structure and parameter uncertainty analysis are suggested to further quantify the benefit of CNHS models in multi-level water resources governance. Highlights: Coupled models can better capture the water diversion and streamflow dynamics The social norms effect is influenced by policy rules and equifinality Different water allocations show the feedback effect of water policy on diversion behaviors